Role of glycated hemoglobin (HBA1c) as a dual marker to predict glycemic status and dyslipidemia in type II diabetes mellitus - Sirsikar, Mangala; S, Supriya; Mohanty, Shrabani; Pinnelli, Venkata Bharat Kumar (International Journal of Research in Medical Sciences, 2016)
Background: Type 2 diabetes mellitus (DM) is an endocrinological disease associated with hyperglycemia characterized by both insulin resistance and defective insulin secretion. Glycated hemoglobin (HbA1c) is a routinely used marker for long-term glycemic control. This study is aimed at investigating the relationship between glycemic control and serum lipid profile and to evaluate the role of glycated haemoglobin as an independent risk factor for cardiovascular diseases in patients with type-2 diabetes and to evaluate the diagnostic value of glycated hemoglobin (HbA1c) in predicting diabetic dyslipidemia as a marker of circulating lipids. The aim of the present study was to estimate glycated hemoglobin and lipid profile in patients with type 2 DM and compare it with controls (healthy subjects). The association of glycated hemoglobin with lipid profile evaluated. Methods: This study was conducted in 150 subjects, out of whom 75 were type 2 diabetes mellitus patients (cases) and 75 were non diabetic healthy subjects (controls).The sera were analyzed for HbA1c, fasting blood glucose (FBG), total cholesterol, triglycerides, high-density lipoprotein cholesterol (HDL) and low-density lipoprotein cholesterol (LDL). Results: A significantly increased level of glycated hemoglobin (HbA1c) is observed in cases compared to control. HbA1c showed direct and significant correlations with cholesterol, triglycerides and LDL and inverse correlation with HDL in cases when compared to controls. Our study also revealed a significant positive correlation between lipid profile and glycated hemoglobin. Conclusions: These findings clearly suggest that HbA1c can provide valuable supplementary information about the extent of circulating lipids besides its primary role in monitoring long-term glycemic control. Further studies are warranted to reinforce the potential of HbA1c as a biomarker for screening of high-risk diabetic patients.